DEFORMATION TREATMENT OF CAST PARTS IN THE PROCESS OF COMPOSITE METALS PRODUCTION AT CROSS-WEDGE ROLLING - V. V. Petrenko (Литьë и металлургия)
The peculiarities of production of bimetallic parts while combining molding processes of cross-wedge rolling are considered. The possibility of manufacturing of a hollow items such as «shaft» in the process of rolling of two different steel parts, namely molded bushing and the base material was shown. It is established that the process of the parts welding occurs due to the high compressive stresses on the interface between two dissimilar metals. As a result along the whole contact area formed a welded joint, the strength of which exceeds 34% of the strength of the steel 45 and judging the microstructure can reach it.